Matrix-dependent high-contrast photochromism in Eu-doped M3MgSi2O8 (M = Ca, Sr, Ba) - Krieke, Guna; Antuzevics, Andris; Kalinko, Aleksandr; Kuzmin, Alexei; Murauskas, Tomas; Kareiva, Aivaras; Zarkov, Aleksej (Royal Society of Chemistry, 2024)
The photochromic properties and charge transfer processes were studied in novel Eu-doped M3MgSi2O8 (M = Ca, Sr, Ba) compounds. These materials exhibit vivid color changes upon irradiation with UV light, resulting in orange, reddish-pink, and green colors. The introduction of europium ions enhances photochromic efficiency and shifts excitation peaks to lower energy ranges. Analysis of diffuse reflectance and electron paramagnetic resonance spectra reveals the formation of both paramagnetic and non-paramagnetic defects, with the dominant signals attributed to electron centers, likely F+-type centers. The Eu2+ → Eu3+ charge transfer during irradiation indicates that Eu2+ acts as a hole center. These findings contribute to a better understanding of the mechanisms underlying photochromism in these materials and highlight their potential for practical applications. © 2024 The Royal Society of Chemistry. --//-- This is an open-access article Krieke, Guna, Antuzevics, Andris, Kalinko, Aleksandr, Kuzmin, Alexei, Murauskas, Tomas, Kareiva, Aivaras, Zarkov, Aleksej, "Matrix-dependent high-contrast photochromism in Eu-doped M3MgSi2O8 (M = Ca, Sr, Ba)", J. Mater. Chem. C, 2024, volume 12, issue 41, pages 16989-16998, doi 10.1039/D4TC03091E published under the CC BY-NC licence.
This project has received funding from the Research Council of Lithuania (LMTLT), agreement no. S-PD-24-67. We acknowledge DESY (Hamburg, Germany), a member of the Helmholtz Association HGF, for the provision of experimental facilities. Part of this research was carried out at the PETRA III synchrotron within proposal no. I-20230821 EC. Institute of Solid State Physics, University of Latvia as the Center of Excellence has received funding from the European Union's Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement no. 739508, project CAMART2.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics